2004
DOI: 10.1200/jco.2004.11.120
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Arginine Deiminase Treatment of Patients With Unresectable Hepatocellular Carcinoma: Results From Phase I/II Studies

Abstract: Elimination of all detectable plasma arginine in patients with HCC was well tolerated and seemed to be effective in the treatment of some patients with HCC. Further testing of ADI-SS PEG 20,000 mw in a larger population of individuals with HCC as well as other human tumors auxotrophic for arginine is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
174
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(185 citation statements)
references
References 32 publications
8
174
0
1
Order By: Relevance
“…These numbers are comparable to those reported from the Pascale Cancer Institute and from a phase I/II trial reported from M.D. Anderson [75]. Interestingly, of the 9 patients treated at the University of Miami, two patients had stable disease for at least 12 months.…”
Section: Clinical Studies With Adi-peg20supporting
confidence: 75%
See 1 more Smart Citation
“…These numbers are comparable to those reported from the Pascale Cancer Institute and from a phase I/II trial reported from M.D. Anderson [75]. Interestingly, of the 9 patients treated at the University of Miami, two patients had stable disease for at least 12 months.…”
Section: Clinical Studies With Adi-peg20supporting
confidence: 75%
“…No toxicity due to the drug was noted. This encouraging response led to a phase I/II trial of ADI-PEG20 in patients with unresectable hepatocellular carcinoma [75]. Patients with hepatocellular carcinoma were accrued from the Pascale Cancer Institute in Naples, Italy.…”
Section: Clinical Studies With Adi-peg20mentioning
confidence: 99%
“…A phase I dose escalation study which combined Adi-PEG 20 with cisplatin and pemetrexed provided a signal of efficacy with a 78% response rate (7 out of 9 patients) (163). These findings are consistent with demonstrated efficacy of arginine depletion therapy in other malignancies (164)(165)(166)(167). A phase 2/3 study is currently recruiting patients with MPM with low ASS1 expression to evaluate the efficacy of Adi PEG 20 in combination with pemetrexed and cisplatin (clinicaltrials.gov NCT02709512).…”
Section: Arginine Depletionsupporting
confidence: 53%
“…The observed 1-h half-life represents many circulation periods and may be sufficient to allow nanotubes that are linked to targeting moieties such as antibodies or peptides to localize in tissues of interest. Moreover, circulation time can probably be significantly extended by PEGylation [poly(ethylene glycol) wrapping] of the nanotube surfaces (16,22). In principle, this may be achieved either by covalent sidewall derivatization or by surrounding the nanotubes with a stable sheath of noncovalently bound PEG-like molecules that will resist displacement by proteins.…”
Section: Resultsmentioning
confidence: 99%